2016
DOI: 10.1007/s10620-016-4126-1
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Interventions Including Nutrition, Exercise, and Supplements for Nonalcoholic Fatty Liver Disease in Children

Abstract: Nonalcoholic fatty liver disease (NAFLD) is the most common cause of liver disease among children. Lifestyle interventions, such as diet and exercise, are frequently recommended. Children with NAFLD have a distinct physiology that is different from obesity alone and has the potential to influence lifestyle treatments. Studies of diet alone in the treatment of pediatric NAFLD have focused on sugar and carbohydrate, but did not indicate any one dietary approach that was superior to another. For children who are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
78
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 69 publications
2
78
0
1
Order By: Relevance
“…Our conclusions on diet and lifestyle are similar to those reached by other systematic reviews, 13,14 including Africa et al, 14 who also assessed nonrandomized trials. We have suggested that antioxidants (as a class) improve lobular inflammation, following results of CBDR, which were not available to Sarkhy et al 15 This review found the evidence on PUFA to be encouraging but due to variation in formulation and dosing used in trials, our conclusions are more measured than those from Chen et al 16 This analysis has highlighted the limitations of the current data for the treatment of pediatric NAFLD.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our conclusions on diet and lifestyle are similar to those reached by other systematic reviews, 13,14 including Africa et al, 14 who also assessed nonrandomized trials. We have suggested that antioxidants (as a class) improve lobular inflammation, following results of CBDR, which were not available to Sarkhy et al 15 This review found the evidence on PUFA to be encouraging but due to variation in formulation and dosing used in trials, our conclusions are more measured than those from Chen et al 16 This analysis has highlighted the limitations of the current data for the treatment of pediatric NAFLD.…”
Section: Discussionsupporting
confidence: 89%
“…10 There are no licensed or uniformly recommended pharmacological therapies and bariatric surgery is only recommended if there are additional comorbidities. 11 The conclusions of other systematic reviews in the field have been limited to specific treatment modalities [12][13][14] or pharmacological options, [15][16][17] or have not distinguished children from adults. 18 One of the biggest challenges in designing a robust randomized controlled trial (RCT) in pediatric NAFLD is the lack of societal consensus on appropriate primary outcome measures.…”
mentioning
confidence: 99%
“…Despite the great attention which is devoted in Europe to healthier environment and to urban mobility, using the paradigm of smart city, few or no research are at the moment published and available, even if elsewhere there is already a move in this sense also by comprehensive approach focused to clinical risk assessment and management[2]. The important most recent reviews appropriately address benefits of healthy diet and exercise on NAFLD[27] both in adults[28] and in children[29], even if other factors, genetic[30], behavioural and environmental should not be neglected[31,32]. The opportunity for the medicine are relevant since articulated clinical intervention, which, according to our results, are justified, can be pursued with a focus on nutritional profile, physical exercise mainly open-air for enhancing sun exposure and improving sleep duration and rhythm[33], cultural and traditional medicine issues and, comprehensively, the quality of life[34-39].…”
Section: Discussionmentioning
confidence: 99%
“…Africa et al [7] recently reviewed twenty-eight studies of lifestyle interventions on children with NAFLD. Among them, only a minority achieved a significant improvement of hepatic outcome measures, such as serum alanine aminotransferase (ALT), and a hepatic fat fraction or histological scores.…”
Section: Introductionmentioning
confidence: 99%